Decellularized pancreas as a native extracellular matrix scaffold for pancreatic islet seeding and culture. (10th April 2018) - Guruswamy Damodaran, Rajesh; Vermette, Patrick
Abstract: Diabetes mellitus involves the loss of function and/or absolute numbers of insulin‐producing β cells in pancreatic islets. Islet transplantation is currently being investigated as a potential cure, and advances in tissue engineering methods can be used to improve pancreatic islets survival and functionality. Transplanted islets experience anoikis, hypoxia, and inflammation‐mediated immune response, leading to early damage and subsequent failure of the graft. Recent development in tissue engineering enables the use of decellularized organs as scaffolds for cell therapies. Decellularized pancreas could be a suitable scaffold as it can retain the native extracellular matrix and vasculature. In this study, mouse pancreata were decellularized by perfusion using 0.5% sodium dodecyl sulfate. Different characterizations revealed that the resulting matrix was free of cells and retained part of the pancreas extracellular matrix including the vasculature and its internal elastic basal lamina, the ducts with their basal membrane, and the glycosaminoglycan and collagen structures. Islets were infused into the ductal system of decellularized pancreata, and glucose‐stimulated insulin secretion results confirmed their functionality after 48 hr. Also, recellularizing the decellularized pancreas with green fluorescent protein‐tagged INS‐1 cells and culturing the system over 120 days confirmed the biocompatibility and non‐toxic nature of the scaffold. Green fluorescent protein‐tagged INS‐1 cells formed pseudoislets that were, over time, budding out of the decellularized pancreata. Decellularized pancreatic scaffolds seeded with endocrine pancreatic tissue could be a potential bioengineered organ for transplantation.